2014
DOI: 10.1080/09243046.2014.944254
|View full text |Cite
|
Sign up to set email alerts
|

The effect of silica nanoparticles, thermal stability, and modeling of the curing kinetics of epoxy/silica nanocomposite

Abstract: A nanocomposite was synthesized using silica nanoparticles (SN) and Epoxy Vinyl Ester Resin (VE671). Nanoparticles were dispersed in the mixture by ultrasonic equipment to prevent the agglomeration. Transmission electron microscopy was used to investigate the dispersion of the SN in the mixture. Non-isothermal differential scanning calorimetry technique was used to study the cure kinetics of VE671 resin with and without adding SN. The activation energy (E a ) was determined using Kissinger and Ozawa equations.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 31 publications
0
17
0
Order By: Relevance
“…At higher temperatures, the SNPs move toward the surface because of silica's low surface potential energy. This silica acts as a thermal insulator and protects the polymer [29][30][31].…”
Section: Field Emission Scanning Electron Microscopy (Fe-sem)mentioning
confidence: 99%
“…At higher temperatures, the SNPs move toward the surface because of silica's low surface potential energy. This silica acts as a thermal insulator and protects the polymer [29][30][31].…”
Section: Field Emission Scanning Electron Microscopy (Fe-sem)mentioning
confidence: 99%
“…It has been proven that the addition of nanoparticles to polymers can improve many of their final properties, so nanocomposites have attracted more attention, and on that basis, many applications have been developed . Many researchers have studied different nanofillers, such as carbon black, fumed silica, titanium oxide, calcium carbonate, calcium silicate, and alumina, in recent years . There have been many investigations on the improvement of the mechanical, thermal, and electrical properties of epoxy resin .…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers have studied different nanofillers, such as carbon black, fumed silica, titanium oxide, calcium carbonate, calcium silicate, and alumina, in recent years . There have been many investigations on the improvement of the mechanical, thermal, and electrical properties of epoxy resin . Tarrio‐Saavedra et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One possible explanation for this discrepancy may be that the nanoparticles used by Xie et al are larger (60 nm) than those used by Ghosh et al (50 nm). Arabli and Aghili reported a small increase in the IDT for epoxy nanocomposites containing SiO 2 , which is corroborated by Liu et al However, Alzina et al presented the opposite, showing decreased thermal stability with a lower IDT. Guo et al showed small changes in the thermal stability dependent on the type of surface modification used.…”
Section: The Structure–property Relations In Epoxy Nanocompositesmentioning
confidence: 60%